2013
DOI: 10.1002/clc.22180
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30‐Day Readmission in Patients Hospitalized With Decompensated Heart Failure

Abstract: Background: Heart failure (HF) is the leading cause of hospitalizations and readmissions in the United States. Approximately one-third of patients admitted for HF are readmitted within 3 months; however, there are few markers that can identify those at highest risk for readmission. The purpose of this study was to identify clinical and laboratory markers associated with hospital readmission in decompensated HF. Hypothesis: Clinical and laboratory markers are associated with readmission rates in decompensated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In general, hospitalizations for heart failure are more challenging to predict than mortality [2832]. These problems may be magnified in the LVAD population, as the LVAD itself introduces many new reasons for why patients may be rehospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…In general, hospitalizations for heart failure are more challenging to predict than mortality [2832]. These problems may be magnified in the LVAD population, as the LVAD itself introduces many new reasons for why patients may be rehospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum sodium is a known predictor of readmission in patients admitted with acute decompensated heart failure, 26 we found no prior study examining serum sodium levels and readmission following an ACS hospitalization. It may also be that sodium levels are a marker for other clinical morbidity or vulnerability that was not captured in the information available in the current study.…”
Section: Discussionmentioning
confidence: 78%
“…Hazard regression modelling with receiver-operating curve analyses yielded three inpatient metrics associated with decreased readmissions (table 1). 23 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, in the absence of a robust risk assessment model to predict increased risk of readmission for patients with HF, there is an ever growing need for studies focusing at identification of clinical and laboratory parameters associated with increased risk of HF readmission and their optimal management. Our group conducted an observational study that identified three discharge metrics (table 1) that resulted in lower incidence of 30-day readmissions for patients with HF 23. The present study is a prospective validation of these discharge criteria with the following objectives:…”
Section: Introductionmentioning
confidence: 99%